The attachment of the adolescent victims of bullying with their father - Fatmawati Fatmawati (Konselor, 2018)
The high statistic of bullying behavior among adolescents is due to the low relationship between adolescents and parents. This happens because basically bullying behavior is influenced by the lack of emotional maturity, that is formed through the attachment of children with their parents, especially fathers. For this reason, this study aimed to find out the type of attachment to fathers among bully adolescents at Sekolah Menengah Pertama Negeri 9 Banda Aceh. Data collection was conducted using Adult Attachment Scale (AAS). The results showed that close attachment to father was mostly in the low category with a percentage of 74.19%, which was then followed by the medium and high categories with the percentage of 16.13% and 9.68% respectively. Next, the anxious attachment style to father was mostly in the high category with a percentage of 67.75%, which was then followed by the medium category of 19.35% and low of 12.90%. Finally, the attachment style of the dependent attachment was mostly in the medium category of 80.65%, while the high and low categories were 9.67% respectively. So it can be concluded that the majority of bully adolescents have anxious attachment style to their fathers.